Loneliness among older adults living with HIV: the "older old" may be less lonely than the "younger old". Issue 3 (4th March 2021) - Mazonson, Peter; Berko, Jeff; Loo, Theoren; Kane, Mark; Zolopa, Andrew; Spinelli, Frank; Karris, Maile; Shalit, Peter
ABSTRACT: Loneliness is common among older (age 50+) people living with HIV (PLWH). However, little is known about the prevalence of loneliness across subgroups of older PLWH, and the factors that impact loneliness. An online questionnaire was used to collect data from 998 older PLWH. Of those, 61% were 50–59 years old and 39% were 60 or older. The majority were male (89%), gay (77%), and white (69%). Fifty-one percent of participants were classified as lonely. The prevalence of loneliness was lower in the older age group, 46.2% vs. 53.8% ( Χ 2  = 5.53, p  = 0.02). Covariates associated with loneliness included being younger, being single, having at least a four-year college degree, living alone, screening positive for depression, using recreational drugs, smoking tobacco, having a lower quality of life, and not feeling close to friends. Logistic regression analysis showed that the "younger old" were at 26% greater risk of loneliness, after controlling for the effects of these covariates (RR 1.26, 95% CI: 1.06–1.45). Reasons why the "older old" were less lonely may include lower rates of depression and lower likelihood of feeling distant from friends. Understanding factors that protect the "older old" against loneliness may provide guidance for future interventions.